2003
DOI: 10.1076/brhm.34.1.61.14081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carotenoid Depletion on the Hatching Rhythm of the Silkworm, Bombyx mori

Abstract: To investigate the functional involvement of carotenoid in the insect circadian rhythm, we observed the effect of carotenoid depletion on the hatching patterns of the silkworm under several light conditions. When eggs were transferred from continuous light (LL) to continuous darkness (DD), an overt hatching rhythm was initiated. The first hatching peak, which was observed at 13.2 h after the transfer in the carotenoid-depleted silkworm, was reduced remarkably in both control groups (carotenoid-rich and caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The wild-type strain used in the present study showed circadian rhythms in hatching and eclosion, as reported in other strains (Tanaka, 1966a; 1966b; 1966c; Oshiki and Watanabe, 1978a, 1978b; Sakamoto and Shimizu, 1994; Sakamoto et al, 2003; Shimizu and Matsui, 1983). In developed embryos of this strain, temporal changes in the expression of per and tim were observed during the day.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The wild-type strain used in the present study showed circadian rhythms in hatching and eclosion, as reported in other strains (Tanaka, 1966a; 1966b; 1966c; Oshiki and Watanabe, 1978a, 1978b; Sakamoto and Shimizu, 1994; Sakamoto et al, 2003; Shimizu and Matsui, 1983). In developed embryos of this strain, temporal changes in the expression of per and tim were observed during the day.…”
Section: Discussionsupporting
confidence: 85%
“…In the hatching rhythm of B. mori , Sakamoto et al (2003) hypothesized that a carotenoid-dependent hourglass mechanism suppresses hatching after lights-off. This mechanism suppresses hatching on the first day under DD conditions and in the scotophase under LD conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the effect of light intensity on the hatching of eggs of Bombyx mori (L.) (Sakamoto et al, 2003) and Bemisia argentifolii Bellows & Perring (Blackmer et al, 2002), that of coloured light on life processes is, less well explored and, a unique aspect of this study.…”
Section: Discussionmentioning
confidence: 96%